2015
DOI: 10.1021/am5079489
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Structure Characteristics, Self-Assembling, and Solvent Compatibility of Holocellulose Nanofibrils

Abstract: Rice straw holocellulose was TEMPO-oxidized and mechanically defibrillated to produce holocellulose nanofibrils (HCNFs) at 33.7% yield (based on original rice straw mass), 4.6% higher yield than cellulose nanofibril (CNF) generated by the same process from pure rice straw cellulose. HCNFs were similar in lateral dimensions (2.92 nm wide, 1.36 nm thick) as CNF, but longer, less surface oxidized (69 vs 85%), and negatively charged (0.80 vs 1.23 mmol/g). HCNFs also showed higher affinity to hydrophobic surfaces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
58
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 35 publications
1
58
0
1
Order By: Relevance
“…Optimized 2,2,6,6-tetramethylpyperidine-1-oxyl (TEMPO) oxidation coupled with mechanical blending produced much thinner (1−3 nm wide) and longer (up to 1 μm long) CNFs at an impressive 96.8% yield. 19,21,22 These CNCs and CNFs showed intriguing self-assembling behaviors that led to ultrafine fibers 23 and amphiphilic superabsorbent aerogels. 24,25 While chemical approaches generated most homogeneous CNCs and CNFs and excellent CNF yield when combined with mechanical blending from rice straw cellulose, mechanical blending alone usually led to low yields.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Optimized 2,2,6,6-tetramethylpyperidine-1-oxyl (TEMPO) oxidation coupled with mechanical blending produced much thinner (1−3 nm wide) and longer (up to 1 μm long) CNFs at an impressive 96.8% yield. 19,21,22 These CNCs and CNFs showed intriguing self-assembling behaviors that led to ultrafine fibers 23 and amphiphilic superabsorbent aerogels. 24,25 While chemical approaches generated most homogeneous CNCs and CNFs and excellent CNF yield when combined with mechanical blending from rice straw cellulose, mechanical blending alone usually led to low yields.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was shown that this material yields nanopaper structures of high quality and optical transparency [8,9]. Residual hemicellulose in fibrillated holocellulose enables improved dispersion of MFC in non-polar solvent [10]. Moreover, holocellulose nanocrystals produced by acid hydrolysis are amphiphilic in surface-chemical terms and capable of stabilising oil-in-water emulsions [11].…”
Section: Introductionmentioning
confidence: 99%
“…The 3D porous PU foam is used as the template because it has mechanical and environmental stability. [37,38] Therefore, we integrated 3D structure of PU foam, oleophilic property and rough surface of GNs, and hydrophilic property of CNWs to construct a superamphiphilic foam (graphene@polyurethane foams, CGPFs) through a facile and green dip-coating process. CNWs, [33] extracted from natural fibers, are abundant biomass materials.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] Furthermore, cellulose nanofibers are used to fabricate amphiphilic materials because of coexisted hydrophilic and oleophilic groups. [37,38] Therefore, we integrated 3D structure of PU foam, oleophilic property and rough surface of GNs, and hydrophilic property of CNWs to construct a superamphiphilic foam (graphene@polyurethane foams, CGPFs) through a facile and green dip-coating process.…”
Section: Introductionmentioning
confidence: 99%